PENETAPAN `ILLAT AL-HUKM MELALUI AL-MANÂTH DALAM QIYÂS - Fahruddin Ali Sabri (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
One method of legal istinbâth agreed upon by the ushul fiqh scholars is al-qiyâs. In al-qiyâs was appeared some serious problems dealing with the search for al-'illat. Al-'illat as one of the obligation of al-qiyâs occupies the most important position, so that the method of al-qiyâs can be applied in the future correctly, and will give legal decision correctly. In searching for al-'illat, the ushul fiqh scholars use logic of linguistic typically in the search for truth, the other hand they also must be able to impulse, imagination, and creativity in decide on a case, and they are no longer so glued rigidly to the al-qath'iyyah al-dalâlah. One way to look for al-'illat is al-manâth, which divided into three parts, namely tanqîh al-manâth, tahqîq al-manâth, and takhrîj al-manâth. Searching for the truth of qiyâs method stresses on logical translation that sometimes mix with intuition, imagination and creativity. Therefore, qiyâs can go down to the law problems related to the people’s attitude deeper. While al-manath is one of the methods to look for al-illat where the ulama ushul fiqh draw their intuition, imagination, and creations to solve some problems, and they are not too stiff to qath’î theoremsCopyright (c) 2015 by Al-Ihkam. All right reserved DOI : 10.19105/al-ihkam.v10i1.587